Manganese metal organic frame work assisted magnetic ionic liquid single crystal - Naima Sharmin; Md. Jahidul Islam (Chemical Physics Impact)
This research focuses on the synthesis and characterization of a Metal-Organic Framework Assisted Ionic Liquid (MOFIL) with the chemical formula of [Mn(Cy)(R)2]R·2H2O; where, Cy is cyclam- (1,4,8,11-tetraazacyclotetradecane) and R is 4-tetradecyloxy benzoate- (4-CH3(CH2)13OC6H4COO-). This novel ionic liquid crystal is synthesized in a multistep process. The first precursor compound ethyl 4-tetradecyloxy benzoate, 4-CH3(CH2)13OC6H4COOC2H5 (A) is obtained from a reaction in between the ethyl 4‑hydroxy benzoate, 4-HOC6H4COOC2H5 and 1-bromotetradecane, CH3(CH2)13Br. Precursor A is further reacted with potassium hydroxide, KOH to yield the 2nd precursor a potassium salt of ethyl 4-tetradecyloxy benzoate, 4-CH3(CH2)13OC6H4COOK (B). Then the precursor B is reacted with manganese chloride tetrahydrate, MnCl2·4H2O to synthesize the dinuclear Manganese (II) carboxylate intermediate compound, [Mn2(R)4(H2O)4] (1). Finally, the addition of cyclam to compound (1) results in the targeted mononuclear MOFIL compound with cyclam, [Mn(Cy)(R)2]R·2H2O (2). This article reports the synthetic procedure and structural elucidation of this MOFIL compound (2) along with its precursors (A and B) and intermediate (1) compound by Fourier Transform Infra-Red (FTIR) spectroscopy, Ultraviolet- Visible (UV- Vis) spectroscopy, and single crystal X-ray crystallography. In addition, the magnetic, thermal, and optical studies of the final MOFIL (2) and its dinuclear intermediate compound (1) are also presented. The dinuclear intermediate, (1) having a higher melting temperature around 150 °C and no development of optical texture as observed by Optical Polarizing Microscope (OPM) and Differential Scanning Calorimetric (DSC) data; doesn't fulfil the criteria of being a MOFIL. In contrast, the mononuclear final compound, (2) with cyclam, is crystallized in triclinic system, showing distorted octahedral N4O2 geometry around a mononuclear d4 Mn(III) centre; that is further evidenced by it's µeff value of 4.6 BM., calculated from room temperature magnetic susceptibility measurement. Compound (2) is thermally stable (Tdec, 242 °C) according to Thermogravimetric Analysis (TGA). It exhibits mesomorphism and behaves as ionic liquid with a melting temperature <110 °C as observed by OPM and DSC data.